RELEVANCE OF THE CONCEPT OF JUSTICE IN THE ECONOMIC PRINCIPLES OF ISLAM - Sri Wahyuni; Ari Asriadi (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to analyze the relevance of the concept of dignified justice in Islamic economic principles. The method used in this study is qualitative research on the basis of writing references. This aspect is taken to elaborate more specifically the views of experts and research both on dignified justice and on the principles of Islamic economics. The sources that researchers use are sources related to themes obtained from journals, books, both national and international which have been published in the last five years. The results of this study show the concept of dignified justice urgent in principle economy Islam. Draft this emphasize treatment which same and fair for all people without except and ensure that all individual and group Public own chance which same for reach well-being economy. Besides that, draft this also role urgent in management source power natural and economy with ensure that source power the used in a manner fair and equally for whole stakeholders interest.